Cybersecurity Awareness and Community Response to Phishing Threats: An Indonesian Social Behavior Analysis - Fadhil Rozi Hendrawan; Arif Rahman Hakim; Dewi Marini Umi Atmaja; Zaidan Mufaddhal (LPPM Universitas Bhinneka Nusantara, 2026)
This research discusses the increased levels of connectivity and digital engagement experienced by the people of Indonesia due to the development of digital technology as well as the risks associated with the growing prevalence of phishing cyber crimes in the country despite having the third-highest population of internet users globally. Although the level of digital literacy varies across different regions in the country, younger users in Indonesia appear to be the most vulnerable to phishing attacks. In view of the above, this paper seeks to identify and explore the behavioral dimensions that determine vulnerability to phishing amongst young internet users in Indonesia through a qualitative exploration of behavioral exposure towards such cyber crime. The research employs a quantitative cross-sectional survey method using structured questionnaires provided to 53 participants in their teens who were frequently involved in using digital platforms for purposes such as engaging on social media, making purchases from e-commerce sites, and executing payments via digital platforms, all chosen using a purposive sample method. Validity and reliability were measured using the Principal Component Analysis, the Kaiser-Meyer-Olkin validity test, Bartlett's Test of Sphericity and Cronbach's Alpha test respectively. Validity tests produced a KMO measure of 0.587 with a statistically significant Bartlett test result (χ²=71.940, df=10, p<0.001). Using PCA, two factors contributing 70.997% cumulative variance were identified with Eigenvalue values of 2.299(45.98%) and 1.251(25.02%). The first factor measures active reception of links via digital platforms and the second measures exposure to bypassing attempts via OTP channels. The four-item scale had a Cronbach Alpha of 0.743 implying acceptable internal consistency.